Mechanical Behaviour of Type 316L Austenitic Stainless Steel in Low Pressure Hydrogen Steam Environment. Issue 1 (August 2021) - Janoušek, J
Abstract: Low pressure superheated H2 -steam appears to be an interesting alternative to pressurized water environments, since it is capable of performing accelerated environmentally assisted cracking (EAC) experiments for nickel base and stainless steel alloys. Constant Extension Rate Tensile (CERT) tests were performed with strain rates of 2 × 10 −6 or 2 × 10 −8 ms −1 at 350, 400, 440 and 480 °C on flat tapered specimens of Type 316L austenitic stainless steel. The tapered shape allows the determination of crack initiation over a range of stresses and strains simultaneously on one specimen and therefore the threshold stress value was obtained. The environment was 6 times more oxidizing than the dissociation pressure of NiO. The acquired mechanical properties are summarized and threshold stresses for EAC crack initiation are evaluated.